Sunflower Bioecophysiology - Yomg’irovna, Rahimova Gulnoza (American Journal of Biology and Natural Sciences, 2025)
Sunflower (Helianthus annuus) — is a common agricultural plant that can produce high yields and has high nutritional value. Its bioecophysiological properties help to understand the importance of climate, soil and water resources in the process of growth and development. Sunflower places high demands on sunlight, heat and fertile soils, as well as the plant’s photosynthesis process and heliotropism (movement towards the sun) increase its efficiency. The plant adapts to special ecological conditions during its growth stages, that is, during the growing season, flowering and spawning periods. Its soil and water requirements play an important role in growth and crop management. Sunflower seeds and oil have a high nutritional value and contain fats and antioxidants that are beneficial for human health. This annotation summarizes the bioecophysiological characteristics and agronomic significance of the sunflower plant, which helps to determine the conditions necessary for its effective cultivation and high quality of the crop. It is possible to grow the plant under optimal conditions, increase its nutritional value and ensure its ecological benefits.